Istraživanje metodičkoga znanja budućih učitelja na primjeru prijelaza između dvaju prikaza - Koray Serin, Mehmet (University of Zagreb Faculty of teacher education, 2021)
The purpose of the study was to examine the pre-service teachers’ transitions between representations and to make inferences about their pedagogical content knowledge. The participants in the study, which was designed as a case study, were 92 senior pre-service teachers attending a state university in Turkey. For data collection, two problems used for fourth-graders in the assessments held by TIMSS in 2007 and 2011 were applied. The participants solved these problems according to their own level and the level of fourth graders. Content analysis was conducted on the collected data. Pre-service teachers dominantly used symbolic (algebraic) representations in their solutions in line with their own level. On the other hand, in their solutions at the level of fourth-graders, a decrease was observed in their use of representations, particularly in the ticket problem in which they experienced difficulties. The rate of using suitable representations in the cake problem was found to be higher. Nearly 30 % of the pre-service teachers managed to solve both of the problems by using representation(s) suitable for the level of primary fourth-graders, as they had sufficient pedagogical content knowledge (PCK).

Svrha ove studije je istražiti prijelaz između prikaza budućih učitelja te doći do zaključaka o njihovom metodičkom znanju. U istraživanju, provedenom kao studiji slučaja sudjelovalo je 92 budućih učitelja, studenata viših godina državnoga fakulteta u Turskoj. Za prikupljanje podataka koristila su se dva zadatka koji su u vrednovanju TIMSS upotrijebljeni za ocjenjivanje učenika četvrtih razreda 2007. i 2011. godine. Sudionici su te zadatke rješavali na osobnoj razini te na razini učenika četvrtih razreda. Provedena je anliza sadržaja na prikupljenim podatcima. Budući učitelji u svojim rješenjima većinom su se koristili simboličkim (algebarskim) prikazima koji su bili u skladu s njihovom razinom. S druge strane, kada su rješavali zadatke na razini učenika četvrtih razreda, primijećena je smanjena uporaba prikaza, osobito u zadatku s ulaznicom. Postotak uporabe prikladnih prikaza u zadatku s tortom bio je viši. Gotovo 30 % budućih učitelja uspjelo je riješiti oba zadatka koristeći se prikazima prikladnima za razinu učenika četvrtih razreda jer su imali dovoljno metodičkoga znanja.
Keywords: pedagogical content knowledge; metodičko znanje (PCK); pre-service primary school teachers; budući učitelji; multiple representations; višestruki prikazi; 4. Education